Ligand-bridged dinuclear carbonyl compounds of rutheniun and osmium - Mushonga, Paul (University of Cape Town, 2014)
Includes abstract. === Includes bibliographical references (leaves 26-29). === Ligand-bridged dinuc1ear carbonyl compounds of ruthenium and osmium have been successfully prepared and characterised by various analytical and spectroscopic techniques. X-ray crystal structures have been determined for the osmium complexes [OS2(CO)4(p-02CCsH4FeCsHs)2L2] {L = PPh3 (102), py (103)}. Some of the complexes were then investigated for their catalytic activity in the oxidation of cyc10hexane and octane. In this work, hydrogen peroxide was used as an oxidant and acetonitrile as the solvent. A higher selectivity for the alcohol products over the ketones was observed. The average ratio of alcohols to ketones was found to be 4.56 and 1.76 for cyc10hexane and octane respectively. The complexes [OS2(CO)6(p-02CMeh] (4) [Ru(CO)2(p-02CMe)2]n (86), [Ru2( CO )4(p-02CMe )(p-dppm h] [PF 6] (117) and [Ru2( CO)4(p -( 02CMe h(MeCN)2] (118), were tested as homogeneous catalysts for the isomerisation of terminal alkenes. Complex 4 was inactive while the complex 118 gave a 100 % conversion. It is proposed that the catalysis proceeded via the displacement of one acetonitrile ligand from the metal centre providing a vacant site onto which the substrate coordinated. The redox behaviour of the four complexes [Ru2(CO)2(p-COh(